2018
DOI: 10.1111/jsbm.12446
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Innovativeness, Environmental Competitiveness and Government, Industry and Professional Networks on SME Export Likelihood

Abstract: The purpose of this study is to examine how small to medium‐sized enterprises (SMEs) in different industry segments utilize government, industry, and professional networks and to test the influence of SME innovativeness, environmental competitiveness and network type for SME export likelihood. Previous studies on networks and exports tend to be qualitative and based on small samples. This study adds to previous scholarship by investigating a large database consisting of 2,263 Australian SMEs. Results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 132 publications
(203 reference statements)
1
39
0
Order By: Relevance
“…Gebrewahid and Wald, (2017), in examining the footwear leather industry in Ethiopia, observed that many SMEs from developing countries do not export due to several challenges which include the level of competition in the international marketplace, and limited marketing knowledge and capital. Chang and Webster (2018) also indicate that there is a relationship between government clusters and the likelihood of SMEs' exports.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Gebrewahid and Wald, (2017), in examining the footwear leather industry in Ethiopia, observed that many SMEs from developing countries do not export due to several challenges which include the level of competition in the international marketplace, and limited marketing knowledge and capital. Chang and Webster (2018) also indicate that there is a relationship between government clusters and the likelihood of SMEs' exports.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Finally, we contribute to the recent development of learning capability and innovation, and expand the relationship to the complex context. Prior researches focus on the role of external environment (as environmental competitiveness) [58] or internal environment (environmental dynamism) [59] in the organizational management, and they are reflected simultaneously in few studies. Actually, in the practices of organizational management, organizations often face two types of environment with opposite tensions or paradoxes [50].…”
Section: Plos Onementioning
confidence: 99%
“…Internationalization allows firms to increase their total sales and efficiency, learn from foreign markets, and reduce the risk of depending on a single country [10,31]. The most recent literature [32][33][34][35][36][37][38] identifies a model of high-performing small and medium-sized enterprises characterized by the interplay of three fundamental elements of the international strategy. First, this model involves a sequential internationalization process based on the accumulation of experience and learning [39,40].…”
Section: Theoretical Background: a Configurational Approachmentioning
confidence: 99%